Implementasi Metode Qur’ani Dalam Membentuk Kemandirian Anak Usia Dini Di RA-Al-Ma’mur - Ramadanti, Rizki; Aryani, Rita; Rizawati, Rizawati (Neolectura, 2025)
This study aims to describe the implementation of the Qur'anic method in learning activities at RA Al-Ma'mur and analyze changes in children's independent behavior after the method was implemented. The study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of the study were teachers and early childhood at RA Al-Ma'mur. The results showed that the Qur'anic method was implemented through activities to habituate prayer, memorization of short surahs, dhuha prayer, and the delivery of Islamic stories combined with teacher role models. As a result, children showed increased independence in daily activities, the ability to make simple decisions, and responsibility for personal belongings and group assignments. This study concluded that the Qur'anic method is effective as a character education strategy for early childhood.